An intervention based on the stages of change, health profiles and physical activity levels of overweight and obese adults in Sarawak, Malaysia – a feasibility study - Cheah, Whye Lian; Chang, Ching Thon; Helmy, Hazmi; Wan Manan, Wan Muda (Academy of Family Physicians of Malaysia, 2019)
Introduction: Physical inactivity is the one of the leading causes of major non-communicable diseases in the world. The aim of this study is to assess the feasibility of an intervention program based on the stages of change, physical activity levels and health profiles of selected overweight and obese adults in Sarawak. Methods: This intervention study was carried out using selected overweight and obese adults in Sarawak. A total of 75 participants were placed in the intervention group, and 80 respondents were placed in the control group participated. Respondent-determined weekly aerobic exercise sessions were conducted for six months. The Malay version of the long-form International Physical Activity Questionnaire (IPAQ) and Transtheoretical model of change (TTM) questionnaire were used, together with anthropometric measurements and the collection of venous fasting blood profiles. Data was entered and analyzed using SPSS Version 20. Results: The intervention group had significant better stage transitions compared to the control group (p<0.01). They also had significantly lower total cholesterol, although both groups showed significant results (difference= 0.53, p<0.01; difference= 0.38, p=0.01). The respondent-determined intervention program was effective in improving stage transition; however, an intervention of longer duration could provide more conclusive health outcomes. Conclusion: Physical activity plays a role in assisting overweight and obese adults to be more active and healthier.